Calculation of rail potentials in a DC electrified railway system - Çolak, Kerim; Hakan Hocaoglu, M. Hakan (My University, 2003)
One of the most important problems faced in DC electrified railway systems is the stray currents and related touch potentials. Currents which are deviated from their intended path are termed as the stray currents. In this paper, the stray currents and related rail potentials are calculated for a single fed DC railway system. Analytical formulae for the problem are determined by taking into account proper boundary conditions for a particular system which is located in Istanbul. Presented analytical formulae have shown close agreement with the numerical solutions which have been implemented by using distributed parameters approach. In addition, it is observed that earthing resistance of the system has a great influence on the magnitude of stray currents and related rail potentials. © 2012 Elsevier B.V., All rights reserved.
UPEC 2003, 38th International Universities' Power Engineering Conference -- Thessaloniki -- 62394
Keywords: Rail potentials; Stray currents; Boundary conditions; Computer simulation; DC machinery; Electric grounding; Electric potential; Electric resistance; Electric variables measurement; Leakage currents; Parameter estimation; Electric railroads